2020
DOI: 10.3390/psych2040027
|View full text |Cite
|
Sign up to set email alerts
|

Fatherhood Is Associated with Increased Infidelity and Moderates the Link between Relationship Satisfaction and Infidelity

Abstract: Background: Relationship satisfaction has been identified as an important factor in terms of extradyadic sexual involvement. However, in men, fatherhood might be associated with infidelity by leading to changes in relationship satisfaction and the social life of parents. To date, no study has focused on the association of fatherhood and infidelity, nor the influence of fatherhood on the association between relationship satisfaction and infidelity. Methods: Using a cross-sectional design, 137 fathers and 116 no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 69 publications
(109 reference statements)
1
2
0
1
Order By: Relevance
“…Although few studies explored the link between relationship satisfaction and mate retention specifically, a recent study (Conroy-Beam et al, 2016) observed that individuals who had lower mate value than their partner and their partner had higher mate value in comparison to alternative mates, were more satisfied with their relationship and more likely to perform mate retention behaviors. Adding to this, previous evidence suggests that individuals who are less satisfied with their relationship tend to invest less in the relationship and are more likely to commit infidelity (Lacker et al, 2020), further supporting the assumption that relationship satisfaction monitors costs and benefits of relationships.…”
Section: Attachment Style and Relationship Satisfactionsupporting
confidence: 61%
“…Although few studies explored the link between relationship satisfaction and mate retention specifically, a recent study (Conroy-Beam et al, 2016) observed that individuals who had lower mate value than their partner and their partner had higher mate value in comparison to alternative mates, were more satisfied with their relationship and more likely to perform mate retention behaviors. Adding to this, previous evidence suggests that individuals who are less satisfied with their relationship tend to invest less in the relationship and are more likely to commit infidelity (Lacker et al, 2020), further supporting the assumption that relationship satisfaction monitors costs and benefits of relationships.…”
Section: Attachment Style and Relationship Satisfactionsupporting
confidence: 61%
“…We conducted a systematic review and meta-analysis as well as quality assessment of empirical applications of CM Coutts et al, 2011;Jann et al, 2012;Korndörfer et al, 2014;Hoffmann et al, 2015Hoffmann et al, , 2017Höglinger et al, 2016;Kundt et al, 2017;Heck et al, 2018;Nasirian et al, 2018;Hopp and Speil, 2019;Lehrer et al, 2019;Safiri et al, 2019;Schnapp, 2019;Walzenbach and Hinz, 2019;Meisters et al, 2020b;Özgül, 2020Özgül, k = 7 Kundt, 2014Höglinger and Diekmann, 2017;Höglinger and Jann, 2018;Atsusaka and Stevenson, 2020;Hoffmann et al, 2020;Meisters et al, 2020a;Jerke et al, 2021 CM prevalence (k =18) Nakhaee et al, 2013;Kazemzadeh et al, 2016k = 9 Eslami et al, 2013Waubert de Puiseau et al, 2017;Banayejeddi et al, 2019;Klimas et al, 2019;Vakilian et al, 2019;Jensen, 2020;Lacker et al, 2020;Mieth et al, 2021k = 7 Shamsipour et al, 2014Vakilian et al, 2014Vakilian et al, , 2016Gingerich et al, 2015;…”
Section: Discussionmentioning
confidence: 99%
“…Of these, 49 pairs used specific birthday months with P ranging between 0.08 (1/12 months) and 0.25 (3/12 months). In five cases (Eslami et al, 2013;Nakhaee et al, 2013;Khosravi et al, 2015;Nasirian et al, 2018;Safiri et al, 2019), season (e.g., spring) was used which is open for interpretation Substance use and misuse Nakhaee et al, 2013;Shamsipour et al, 2014;Höglinger et al, 2016;Mirzazadeh et al, 2018;Banayejeddi et al, 2019;Safiri et al, 2019;Özgül, 2020;Canan et al, 2021Shamsipour et al, 2014Mirzazadeh et al, 2018;Safiri et al, 2019 Academic misconduct Coutts et al, 2011;Jann et al, 2012;Höglinger et al, 2016;Hopp and Speil, 2019;Jerke et al, 2021Coutts et al, 2011Jann et al, 2012;Jerke et al, 2021 Corruption, tax evasion, and theft Korndörfer et al, 2014;Kundt, 2014;Gingerich et al, 2015;Höglinger and Jann, 2018;Hopp and Speil, 2019;Oliveros and Gingerich, 2020 Health and STDs Mirzazadeh et al, 2018;Nasirian et al, 2018 Sexual behavior and infidelity Mirzazadeh et al, 2018;Klimas et al, 2019;Lacker et al, 2020 Substance use and misuse Khosravi et al, 2015;Kazemzadeh et al, 2016;Heck et al, 2018;…”
Section: Model Designmentioning
confidence: 99%
See 1 more Smart Citation